Headache: Investigate or not to Investigate? - Eiman Ayesha, Tayyaba Gul Malik, Khalid Farooq (Pakistan Journal of Ophthalmology, 2017)
Purpose: To analyze the need of neuro-imaging in patients presenting with headache. Study Design: Retrospective observational study. Place and Duration of study: Heart and body scan and Ghurki trust teaching hospital, Lahore 2008 to 2015. Material and methods: We retrospectively reviewed clinical and neuro-imaging charts of 5289 patients, who were sent to radiology department for neuro-imaging from 2008 to 2015. The major complaint was headache but associated signs and symptoms included vertigo, weakness of limbs, unconsciousness, Proptosis, road traffic accident (RTA), seizures, visual disturbance, neck stiffness, diplopia, memory loss, ataxia, blood from ear, carcinoma, vomiting, cranial nerve palsy, tinitis, Sleep problems and numbness. Results were divided into normal imaging, ENT problems, Space occupying lesions of brain, vascular pathologies of brain and miscellaneous. Results: There were 5289 patients. The age ranged from 6 to 80 years (mean 48 years) and male to female ratio was 1:1.2. Normal neuro-imaging was seen in 67.25% of the total patients. Space occupying lesions of brain were seen in 16% patients, 7.3% had vascular pathology of brain, 5.05% had ENT problems and 4.36% had miscellaneous findings. Patients having headache associated with Proptosis or bleeding from ears had 100% positive results of neuro-imaging. Headache with sleep disturbances had lowest yield (7.7%). Conclusion: History of headache not associated with any other signs and symptoms should not be an indication for neuro-imaging. Key words: Neuro-imaging, Headache, Space occupying lesions of brain.